Early Results with a New Posterior Chamber Phakic Intraocular Lens in Patients with High Myopia - Yaşa, Dilek (J Ophthalmol, 2018)
PURPOSE: To report clinical results of a foldable, hydrophilic acrylic, single-piece, injectable, posterior chamber phakic intraocular lens (pIOL). MATERIAL AND METHODS: Medical records of patients who underwent posterior chamber phakic IOL (Eyecryl Phakic IOL, Biotech Vision Care, Ahmedabad, India) implantation for surgical correction of myopia were retrospectively reviewed. Only patients with at least a one-year follow-up were included. Manifest refraction, uncorrected distance visual acuity (UDVA), corrected distance visual acuity (CDVA), endothelial cell density (ECD), and pIOL vault were analyzed at 1, 3, 6, and 12 months after surgery. Complications observed during and after surgery were also recorded. RESULTS: The study included 58 eyes of 29 patients. Mean patient age was 32 ± 7 years. Spherical equivalent of manifest refraction was −13.41 ± 3.23 D preoperatively and −0.44 ± 0.55 D postoperatively. Preoperative CDVA was 0.29 ± 0.71 logMAR. Postoperative UDVA and CDVA were 0.21 ± 0.66 and 0.15 ± 0.69 logMAR, respectively, at the 12-month visit. At the 12-month visit, the efficacy index was 1.20 and the safety index was 1.39. Mean ECD was 2713 ± 339 cells/mm(2) at the preoperative visit and 2608 ± 362 cells/mm(2) at the 12-month visit (3.9% loss, p < 0.001). ECD loss from 3 months to 12 months was not statistically significant. No significant cataract formation, significant endothelial cell loss, glaucoma, uveitis, or any other vision-threatening complication was observed. CONCLUSION: Based on postoperative experience, we have found that Eyecryl Phakic IOL is safe and effective for treating high myopia.